(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the study of the concept and features of external forms of assessing the effectiveness of entrepreneurial activity. The author’s definition of the concept of "forms of assessing the effectiveness of entrepreneurial activity" is given. The main features of the forms of assessing the effectiveness of entrepreneurial activity are highlighted, such as: legal certainty of assessment methods; analytical nature of procedures; effectiveness and expediency; legality. Forms of assessing the effectiveness of entrepreneurial activity are classified by the subject of assessment into internal and external forms of implementation. It is established that external assessment of effectiveness is an important tool for controlling and regulating entrepreneurial activity, which also affects the investment attractiveness of a business entity. The author’s definition of the concept of "external forms of assessing the effectiveness of entrepreneurial activity" is proposed. It is argued that external assessment of the effectiveness of entrepreneurial activity is one of the legal forms of state control, which is carried out within the framework of administrative and legal regulation of the economy. It is proved that the results of business efficiency assessment serve as a basis for making management decisions by public bodies and may have legal consequences for business entities. The main features of assessing the effectiveness of entrepreneurial activity are analyzed.